PENGARUH LINGKUNGAN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. SINAR MAS LAND. Tbk TANGERANG - Nur’aini Marzani; Donny Dharmawan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
Work environment is one of the factors that affect employee performance. If the environment around the workplace gives an uncomfortable impression, employees feel lazy to work. This study aims to analyze the influence of work environment, competence to employees of PT. Sinar Mas Land, Tbk in Tangerang. Population and sample are all employees of HR division of PT. Sinar Mas Land a total of 30 people. Sampling technique using saturated samples. The results showed that there is a significant influence partially or simultaneously between the work environment on employee performance in PT. Sinar Mas Land Tbk Tangerang area